White Feather - MacPhail, Catherine (Edinburgh: Barrington Stoke Ltd, 2019)
The war is won but for Charlie there is little to celebrate. His brother never returned from no man's land and has died not as a hero but executed as a coward. Refusing to believe that his brother was a traitor, a grief stricken Charlie is pushed to the edge in his dark quest to uncover the horrifying truth. A thrilling narrative of intertwining perspectives
Keywords: Fiction